A degradable composite material and preparation method thereof

By hydrophobic modification of wood powder and blending it with modified chitosan and polylactic acid, the problem of insufficient flame retardancy and antibacterial properties of wood-plastic composites is solved, and its flame retardancy, antibacterial properties and mechanics are significantly improved. Performance improves comprehensive performance and extends service life.

CN118480273BActive Publication Date: 2024-12-27GUANGDONG NATURE HOME FURNISHING TECH RES CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202410586878.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-05-13
Publication Date
2024-12-27
Estimated Expiration
2044-05-13

AI Technical Summary

Technical Problem

Existing wood-plastic composites burn rapidly during fire, have poor flame retardant properties, and insufficient antibacterial properties, resulting in a decline in material performance and shortened service life, limiting its application range.

Method used

By hydrophobic modification of wood powder and melt blending with modified chitosan and polylactic acid, a composite material with excellent biodegradability is prepared. The modified chitosan improves its resistance through esterification and condensation reactions Flammability and antibacterial properties enhance compatibility with polylactic acid.

Benefits of technology

It significantly improves the flame retardancy, antibacteriality and mechanical properties of composite materials, extends the service life, and improves the comprehensive performance, meeting higher application needs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention discloses a degradable composite material and a preparation method thereof, and belongs to the technical field of wood-plastic composite materials. The raw materials are calculated by weight as follows: 50-60 parts of wood powder, 100-120 parts of ether, 12-16 parts of octanoyl chloride, 10-15 parts of modified chitosan, 25-35 parts of polylactic acid, 2-4 parts of plasticizer, 0.1-0.3 parts of catalyst, and 3-5 parts of lubricant. The main raw materials for preparing the composite material are wood powder and polylactic acid, which have excellent biodegradability; the wood powder is modified to improve the compatibility with polylactic acid; wherein the modified chitosan has good compatibility with polylactic acid, significantly enhances the flame retardancy, antibacterial and mechanical properties of the material, and has stable performance. Therefore, the composite material prepared by the present invention has stable and efficient flame retardancy, antibacterial and mechanical properties, and has good degradability, excellent comprehensive performance, and has important application value in the technical field of wood-plastic composite materials.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of wood-plastic composite materials, and in particular relates to a degradable composite material and a preparation method thereof. Background Art

[0002] Wood-plastic composite materials are a new type of biodegradable material that has developed rapidly in recent years. They are made of plastic, wood powder, rice bran and other agricultural and forestry scraps as the main raw materials, and a small amount of additives are added, and they are extruded at high temperature. They are anti-corrosive, moisture-proof, highly dimensional stable, non-cracking, non-warping, and free of toxic components. They have the dual advantages of plastic and wood, and are a new type of wood-like material that can be reversibly recycled. They have great social significance and economic value, especially in the field of furniture decoration.

[0003] Traditional wood-plastic composite materials are generally based on non-degradable plastics such as PP, PE, and PVC. Although the amount of degradable plant fibers such as wood powder used far exceeds the amount of plastic, making it have better degradation performance, it still cannot achieve 100% degradation and will still have a certain impact on the environment after being discarded. For this reason, wood-plastic composite materials prepared with degradable plastics as the matrix are receiving more and more attention.

[0004] Common degradable plastics include PBAT, PLA, PBS, etc. Among them, polylactic acid (PLA) is a polyester polymer obtained by polymerization with lactic acid as the main raw material. Its raw material is made of starch raw materials from renewable plant resources. After use, it can be completely degraded by microorganisms in nature, and finally generate carbon dioxide and water. Its source and post-treatment are extremely environmentally friendly, and it is an ideal green polymer material. However, polylactic acid has a low oxygen index, and the flame retardant properties of wood-plastic composite materials made of plant fibers such as wood powder are poor. When encountering a fire, it burns quickly, seriously affecting people's life safety; in addition, wood-plastic composite materials are often used for home decoration. After being installed and applied, they will be eroded by biological factors such as fungi, bacteria, termites, algae, and marine organisms. The existing wood-plastic composite materials have poor antibacterial properties, which will cause the performance of the material to decline during use, shorten its service life, and limit its scope of use. Therefore, the above problems need to be solved to meet the higher demands in the field of wood-plastic composite technology. Summary of the invention

[0005] The purpose of the present invention is to overcome the defects of the prior art and provide a degradable composite material and a preparation method thereof.

[0006] The purpose of the present invention can be achieved through the following technical solutions:

[0007] A method for preparing a degradable composite material comprises the following steps:

[0008] A1. Immerse the wood powder in ether and stir evenly, then add caprylyl chloride dropwise, and carry out esterification reaction at 30°C for 2 hours. After the reaction is completed, rinse repeatedly with ethanol, and place in an oven at 60°C for 1 hour to obtain modified wood powder;

[0009] A2. Add the modified wood powder, modified chitosan, polylactic acid, plasticizer, catalyst and lubricant obtained in step A1 into a twin-screw extruder for melt blending, extrusion, granulation and injection molding to obtain a degradable composite material.

[0010] Furthermore, the raw materials are calculated in parts by weight as follows: 50-60 parts of wood flour, 100-120 parts of ether, 12-16 parts of octanoyl chloride, 10-15 parts of modified chitosan, 25-35 parts of polylactic acid, 2-4 parts of plasticizer, 0.1-0.3 parts of catalyst, and 3-5 parts of lubricant.

[0011] Furthermore, the plasticizer is di-n-octyl phthalate or dibutyl phthalate.

[0012] Furthermore, the catalyst is stannous chloride or stannous oxide.

[0013] Furthermore, the lubricant is epoxidized soybean oil or paraffin.

[0014] The main raw materials for making the composite material are wood powder and polylactic acid, which have excellent biodegradable properties. In addition, by hydrophobically modifying the wood powder, the compatibility with polylactic acid is improved, which promotes the dispersion of the wood powder. The resulting material has the dual advantages of plastic and wood, and its comprehensive performance is higher than that of ordinary wood or plastic.

[0015] Further, the modified chitosan is prepared by the following steps:

[0016] S1. After phosphorus oxychloride, pentaerythritol and toluene are uniformly stirred in a three-necked flask equipped with a stirring reflux device, nitrogen is introduced, and the temperature is raised to 70°C. After reacting for 2 hours, the temperature is raised to 107°C, and reflux reaction is carried out until no hydrogen chloride gas is generated. After the reaction is completed, the mixture is cooled to room temperature, washed with ether, benzene and dichloromethane in sequence, the solvent is removed by distillation under reduced pressure, and vacuum dried to obtain intermediate 1; the ratio of phosphorus oxychloride, pentaerythritol and toluene is 33.4g:13.6g:75mL;

[0017] Phosphorus oxychloride and pentaerythritol undergo esterification reaction, and the phosphorus oxychloride is in excess to obtain intermediate 1; the specific reaction process is as follows:

[0018]

[0019] S2. At room temperature, under nitrogen protection, in a three-necked flask equipped with a stirring reflux device, mix intermediate 1, n-decylamine, triethylamine and toluene, stir until the solid is completely dissolved, heat to 75°C and keep the reaction for 4 hours. After the reaction is complete, filter and distill under reduced pressure to obtain intermediate 2; the ratio of intermediate 1, n-decylamine, triethylamine and toluene is 30.7g:15.7g:15mL:75mL;

[0020] Intermediate 1 and n-decylamine undergo nucleophilic substitution, and by controlling the molar ratio of the two to be close to 1:1 and a slight excess of intermediate 1, only one chlorine group on intermediate 1 participates in the reaction, and triethylamine removes the hydrogen chloride generated by the reaction to obtain intermediate 2; the specific reaction process is as follows:

[0021]

[0022] S3. In a three-necked flask equipped with a stirring device, 3,5-dihydroxybenzaldehyde, intermediate 2 and toluene were mixed and stirred until the solid was completely dissolved, and then dibutyltin oxide (catalyst) and triethylamine were added, and the temperature was controlled to react for 3 hours at 60°C. After the reaction was completed, the mixture was filtered, and part of the solvent was removed by distillation under reduced pressure. The mixture was purified by column chromatography (the eluent was a mixed solvent of ethyl acetate / benzene in a volume ratio of 7:3), and the eluent was removed by rotary evaporation to obtain intermediate 3; the ratio of the amount of 3,5-dihydroxybenzaldehyde, intermediate 2, toluene, dibutyltin oxide and triethylamine was 15.2 g:41.7 g:100 mL:0.2 g:15 mL;

[0023] Under the catalysis of dibutyltin oxide, 3,5-dihydroxybenzaldehyde and intermediate 2 undergo esterification reaction. By controlling the molar ratio of the two to be close to 1:1 and a slight excess of 3,5-dihydroxybenzaldehyde, only one hydroxyl group on 3,5-dihydroxybenzaldehyde participates in the reaction, and triethylamine removes the hydrogen chloride generated by the reaction to obtain intermediate 3. The specific reaction process is as follows:

[0024]

[0025] S4, chitosan was added to the mixed solution of acetic acid and toluene, stirred until completely dissolved, then intermediate 3 and piperidine (condensing agent) were added, stirred at room temperature for 1 hour, sodium hydroxide solution was added dropwise to adjust the pH to 5.5, and the reaction was continued for 1.5 hours. After the reaction was completed, the mixture was allowed to stand for precipitation, filtered, washed with ethanol and water in turn, and dried in an oven to obtain modified chitosan; the ratio of the mixed solution of acetic acid and toluene, chitosan, intermediate 3, and piperidine was 150mL:1g:73.6g::10mL;

[0026] Under the action of the condensing agent, the aldehyde group on the intermediate 3 condenses with the amino group on the chitosan to form an imine group (C=N Schiff base structure) to obtain modified chitosan; the specific reaction process is as follows:

[0027]

[0028] Chitosan is a polysaccharide with biodegradability and certain antibacterial properties. In addition, a large number of hydroxyl groups in the molecule can promote the dehydration of the matrix into carbon, converting the matrix into a high-concentration carbon layer, thereby improving the flame retardant properties of the matrix. Chitosan has a similar structure to cellulose and has good compatibility with the wood powder matrix. Moreover, by modifying chitosan, its hydrophobicity is improved, the compatibility of chitosan with polylactic acid is improved, and the dispersion of modified chitosan in the matrix is ​​promoted, so that the antibacterial and flame retardant properties of chitosan are fully exerted. In addition, the modified chitosan molecular chain also contains spirocyclic phosphate, Schiff base structure, and long carbon chain structure. Among them, spirocyclic phosphate has a good flame retardant effect and It has a stable six-membered heterocyclic structure. When burning, the pentaerythritol skeleton will form a char protective layer to inhibit further combustion of the matrix, and connect with the N element to form a PN flame retardant component, which has the synergistic flame retardant effect of phosphorus and nitrogen flame retardants, further enhancing the flame retardant properties of the matrix; the introduction of the Schiff base structure can interact with bacterial proteins and enzymes, hindering the synthesis of bacterial nucleotides and amino acids, and can play a synergistic antibacterial role with chitosan; the introduction of a long carbon chain structure can not only penetrate between the macromolecular chains of the matrix to improve the toughness of the matrix, but also the long carbon chain has strong hydrophobicity, which can promote the interaction between chitosan and bacterial cell walls, further enhancing the antibacterial properties of the matrix;

[0029] It should be noted that one end of the modified chitosan contains a hydroxyl group, which can form a chemical bond with polylactic acid under the action of a catalyst to improve the stability of the modified chitosan.

[0030] Beneficial effects of the present invention:

[0031] 1. The main raw materials of the composite material prepared by the present invention are wood powder and polylactic acid, which have excellent biodegradability;

[0032] 2. By hydrophobically modifying wood powder, the compatibility with polylactic acid is significantly improved compared with ordinary wood powder, making the comprehensive performance of the prepared composite material higher than that of ordinary wood or plastic;

[0033] 3. Compared with ordinary chitosan, the prepared modified chitosan has enhanced hydrophobicity and improved compatibility with polylactic acid. It can significantly enhance the flame retardancy, antibacterial and mechanical properties of the composite material, and has stable performance.

[0034] Therefore, the composite material prepared by the present invention has stable and efficient flame retardancy, antibacterial and mechanical properties, good degradability, excellent comprehensive performance, and has important application value in the technical field of wood-plastic composite materials. DETAILED DESCRIPTION

[0035] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0036] Example 1

[0037] Preparation of modified chitosan:

[0038] S1. In a three-necked flask equipped with a stirring reflux device, 33.4 g of phosphorus oxychloride, 13.6 g of pentaerythritol and 75 mL of toluene were stirred evenly, nitrogen was introduced, and the temperature was raised to 70°C. After reacting for 2 hours, the temperature was raised to 107°C, and refluxed until no hydrogen chloride gas was generated. After the reaction was completed, the mixture was cooled to room temperature, washed with ether, benzene and dichloromethane in sequence, the solvent was removed by distillation under reduced pressure, and vacuum dried to obtain intermediate 1;

[0039] S2. At room temperature, under nitrogen protection, in a three-necked flask equipped with a stirring reflux device, 30.7 g of intermediate 1, 15.7 g of n-decylamine, 15 mL of triethylamine and 75 mL of toluene were mixed, stirred until the solid was completely dissolved, and the temperature was raised to 75°C for 4 hours. After the reaction was completed, the mixture was filtered and distilled under reduced pressure to obtain intermediate 2;

[0040] S3, in a three-necked flask equipped with a stirring device, 15.2g 3,5-dihydroxybenzaldehyde, 41.7g intermediate 2 and 100mL toluene were mixed, stirred until the solid was completely dissolved, and then 0.2g dibutyltin oxide and 15mL triethylamine were added, and the temperature was controlled to react at 60°C for 3h. After the reaction was completed, it was filtered, and part of the solvent was distilled off under reduced pressure, and then purified by column chromatography (the eluent was a mixed solvent of ethyl acetate / benzene, and the volume ratio of the two was 7:3), and the eluent was removed by rotary evaporation to obtain intermediate 3;

[0041] S4. Add 1 g of chitosan (relative molecular weight 1000) to a mixed solution of 150 mL of acetic acid and toluene (the mass fraction of acetic acid is 36%), stir until completely dissolved, then add 73.6 g of intermediate 3 and 10 mL of piperidine, stir and react at room temperature for 1 h, add dropwise sodium hydroxide solution (concentration 0.1 mol / L) to adjust the pH to 5.5, continue the reaction for 1.5 h, and after the reaction is completed, let it stand and precipitate, filter, wash with ethanol and water in turn, and dry in an oven to obtain modified chitosan.

[0042] Example 2

[0043] Preparation of modified chitosan:

[0044] S1. In a three-necked flask equipped with a stirring reflux device, 66.8 g of phosphorus oxychloride, 27.2 g of pentaerythritol and 150 mL of toluene were stirred evenly, nitrogen was introduced, and the temperature was raised to 70° C. After reacting for 2 h, the temperature was raised to 107° C. and refluxed until no hydrogen chloride gas was generated. After the reaction was completed, the mixture was cooled to room temperature, washed with ether, benzene and dichloromethane in sequence, the solvent was removed by distillation under reduced pressure, and vacuum dried to obtain intermediate 1;

[0045] S2. At room temperature, under nitrogen protection, in a three-necked flask equipped with a stirring reflux device, 61.4 g of intermediate 1, 31.4 g of n-decylamine, 30 mL of triethylamine and 150 mL of toluene were mixed, stirred until the solid was completely dissolved, and the temperature was raised to 75°C for 4 hours. After the reaction was completed, the mixture was filtered and distilled under reduced pressure to obtain intermediate 2;

[0046] S3, in a three-necked flask equipped with a stirring device, 30.4g 3,5-dihydroxybenzaldehyde, 83.4g intermediate 2 and 200mL toluene were mixed, stirred until the solid was completely dissolved, and then 0.4g dibutyltin oxide and 30mL triethylamine were added, and the temperature was controlled to react at 60°C for 3h. After the reaction was completed, it was filtered, and part of the solvent was distilled off under reduced pressure, and then purified by column chromatography (the eluent was a mixed solvent of ethyl acetate / benzene, and the volume ratio of the two was 7:3), and the eluent was removed by rotary evaporation to obtain intermediate 3;

[0047] S4. Add 2 g of chitosan (relative molecular weight 1000) to a mixed solution of 300 mL of acetic acid and toluene (the mass fraction of acetic acid is 36%), stir until completely dissolved, then add 147.2 g of intermediate 3 and 20 mL of piperidine, stir and react at room temperature for 1 h, add dropwise sodium hydroxide solution (concentration 0.1 mol / L) to adjust the pH to 5.5, continue the reaction for 1.5 h, and after the reaction is completed, let it stand and precipitate, filter, wash with ethanol and water in turn, and dry in an oven to obtain modified chitosan.

[0048] Example 3

[0049] A1. Immerse 50g of wood powder in 100g of ether and stir evenly, then add 12g of octanoyl chloride dropwise, and carry out esterification reaction at 30°C for 2h. After the reaction is completed, rinse repeatedly with ethanol and place in an oven at 60°C for 1 hour to obtain modified wood powder;

[0050] A2. Add the modified wood powder obtained in step A1, 10 g of the modified chitosan obtained in Example 1, 25 g of polylactic acid (Zhejiang Haizheng Biomaterial Co., Ltd., model 110), 2 g of di-n-octyl phthalate, 0.1 g of stannous chloride, and 3 g of epoxy soybean oil into a twin-screw extruder for melt blending, extrusion, granulation, and injection molding to obtain a degradable composite material.

[0051] Example 4

[0052] A1. Immerse 55 g of wood powder in 110 g of ether and stir evenly, then drop 14 g of octanoyl chloride and perform esterification reaction at 30 ° C for 2 h. After the reaction is completed, rinse repeatedly with ethanol and place in an oven at 60 ° C for 1 hour to obtain modified wood powder;

[0053] A2. Add the modified wood powder obtained in step A1, 12.5 g of modified chitosan obtained in Example 2, 30 g of polylactic acid (Zhejiang Haizheng Biomaterial Co., Ltd., Model 110), 3 g of di-n-octyl phthalate, 0.2 g of stannous oxide, and 4 g of paraffin into a twin-screw extruder for melt blending, extrusion, granulation, and injection molding to obtain a degradable composite material.

[0054] Example 5

[0055] A1. Immerse 60 g of wood powder in 120 g of ether and stir evenly, then add 16 g of octanoyl chloride dropwise, and carry out esterification reaction at 30 ° C for 2 h. After the reaction is completed, rinse repeatedly with ethanol and place in an oven at 60 ° C for 1 hour to obtain modified wood powder;

[0056] A2. Add the modified wood powder obtained in step A1, 15 g of modified chitosan obtained in Example 2, 35 g of polylactic acid (Zhejiang Haizheng Biomaterial Co., Ltd., model 110), 4 g of di-n-octyl phthalate, 0.3 g of stannous oxide, and 5 g of paraffin into a twin-screw extruder for melt blending, extrusion, granulation, and injection molding to obtain a degradable composite material.

[0057] Comparative Example 1

[0058] The modified chitosan in Example 5 was replaced by ordinary chitosan of the same mass, and the remaining steps were the same as in Example 5.

[0059] Comparative Example 2

[0060] A commercially available wood-plastic composite material produced by Sichuan Xinqianding Wood Industry Co., Ltd. was used.

[0061] Examples 3-5 and comparative examples 1-2 were made into corresponding shapes according to different test standards and subjected to the following performance tests:

[0062] The impact resistance is measured using the national standard GB / T 1043.1-2008 "Determination of impact properties of simply supported plastic beams Part 1: Non-instrumented impact test";

[0063] The tensile properties are determined using the national standard GB / T 1040.2-2006 "Determination of tensile properties of plastics Part 2: Test conditions for molded and extruded plastics";

[0064] The national standard GB / T 8924-2005 "Fiber reinforced plastic combustion performance test method oxygen index method" is used to determine the limiting oxygen index;

[0065] The antibacterial rate of Staphylococcus aureus and Escherichia coli before and after 90 days of storage was determined using QB / T 2591-2003A "Test methods and antibacterial effects of antibacterial plastics";

[0066] The measured results are shown in the following table:

[0067]

[0068]

[0069] It can be seen from the above table that the flame retardancy, antibacterial properties and mechanical properties of the composite material prepared in the embodiment of the present invention are higher than those of the comparative example, and the comprehensive performance is excellent. Moreover, as the amount of modified chitosan increases, various properties are improved. Therefore, the composite material prepared in the present invention has important application value in the technical field of wood-plastic composite materials.

[0070] In the description of the specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.

[0071] The above contents are merely examples and explanations of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the invention or exceed the scope defined by the claims, they shall all fall within the protection scope of the present invention.

Claims

1. A degradable composite material, characterized in that: The invention comprises the following raw materials in parts by weight: 50-60 parts of wood flour, 100-120 parts of ether, 12-16 parts of octanoyl chloride, 10-15 parts of modified chitosan, 25-35 parts of polylactic acid, 2-4 parts of plasticizer, 0.1-0.3 parts of catalyst and 3-5 parts of lubricant; The method for preparing the degradable composite material comprises the following steps: The wood powder is immersed in ether and stirred evenly, and then octanoyl chloride is added dropwise, and an esterification reaction is carried out at 30° C. for 2 hours. After the reaction is completed, the mixture is repeatedly rinsed with ethanol and dried to obtain modified wood powder; the modified wood powder, modified chitosan, polylactic acid, plasticizer, catalyst, and lubricant are added into a twin-screw extruder for melt blending, extrusion, granulation, and injection molding to obtain a degradable composite material; Wherein, the modified chitosan is prepared by the following steps: S1. After phosphorus oxychloride, pentaerythritol and toluene are uniformly stirred, nitrogen is introduced, and the mixture is reacted at 70° C. for 2 h. The temperature is then raised to 107° C. and refluxed to react until no hydrogen chloride gas is generated. After the reaction is completed, the mixture is cooled, washed, distilled under reduced pressure, and dried under vacuum to obtain intermediate 1. S2, at room temperature, under nitrogen protection, mix intermediate 1, n-decylamine, triethylamine and toluene, stir until the solid is completely dissolved, react at 75°C for 4 hours, filter, and distill under reduced pressure to obtain intermediate 2; S3, 3,5-dihydroxybenzaldehyde, intermediate 2 and toluene were mixed and stirred until the solid was completely dissolved, and then dibutyltin oxide and triethylamine were added, and the mixture was reacted at 60°C for 3 hours. After the reaction was completed, the mixture was filtered, distilled under reduced pressure, purified by column chromatography, and rotary evaporated to obtain intermediate 3; S4. Add chitosan to the mixed solution of acetic acid and toluene, stir until completely dissolved, then add intermediate 3 and piperidine, stir and react at room temperature for 1 hour, add sodium hydroxide solution dropwise to adjust the pH to 5.5, continue the reaction for 1.5 hours, and after the reaction is completed, let it stand and precipitate, filter, wash and dry to obtain modified chitosan.

2. A degradable composite material according to claim 1, characterized in that: In step S1, the ratio of phosphorus oxychloride, pentaerythritol and toluene is 33.4 g:13.6 g:75 mL.

3. A degradable composite material according to claim 1, characterized in that: In step S2, the ratio of the amount of intermediate 1, n-decylamine, triethylamine and toluene is 30.7 g:15.7 g:15 mL:75 mL.

4. The degradable composite material according to claim 1, characterized in that: In step S3, the ratio of the amount of 3,5-dihydroxybenzaldehyde, intermediate 2, toluene, dibutyltin oxide and triethylamine is 15.2 g:41.7 g:100 mL:0.2 g:15 mL.

5. The degradable composite material according to claim 1, characterized in that: In step S4, the ratio of the mixed solution of acetic acid and toluene, chitosan, intermediate 3, and piperidine is 150 mL: 1 g: 73.6 g: 10 mL.

6. The degradable composite material according to claim 1, characterized in that: The plasticizer is di-n-octyl phthalate or dibutyl phthalate.

7. The degradable composite material according to claim 1, characterized in that: The catalyst is stannous chloride or stannous oxide.

8. The degradable composite material according to claim 1, characterized in that: The lubricant is epoxidized soybean oil or paraffin.